Perancangan Mesin Pengurai Sabut Kelapa Berbasiskan Metode Quality Function Deployment (QFD) - Nuriyadi, Nuriyadi; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Generally, coconut farmers in areas of Indragiri Hilir have not exploited waste plantation of coconut in theform of coir. There is only a small portion of them utilize the coir to be processed further but the processing ismanually or traditionally. Whereas coconut husk if it is processed properly that can increase the economicvalue of the coir and also can support the economic community. To overcome these problems, the design ofcoconut coir machine is conduced in this research. This design uses the method of Quality FunctionDeployment (QFD) as the design basis that aims to get the design parameters in accordance with the wishes ofthe community. From the ranking of house of quality (HOQ) which become the main priority in design of thiscoconut coir decomposer machine is ergonomic design, with the total value of importance of 159. The secondpriority is the tool dimension with the total value of importance of 93.12, And the third priority is the selectionof materials and components supporting the engineers of coconut coir, with a total value of interest 89.75. Theselection of the main material and components are: selection of the decomposer blade, selection of the drivingmotor, selection of the pulleys and belts, the selection of the shaft, the choice of bearings, the choice of steelplate, the selection of the profi L steel.Keywords : Coconut coir machine, QFD, HOQ